2014
DOI: 10.1007/s00484-014-0921-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of weather conditions on emergency ambulance calls for acute coronary syndromes

Abstract: The aim of this study was to evaluate the relationship between weather conditions and daily emergency ambulance calls for acute coronary syndromes (ACS). The study included data on 3631 patients who called the ambulance for chest pain and were admitted to the department of cardiology as patients with ACS. We investigated the effect of daily air temperature (T), barometric pressure (BP), relative humidity, and wind speed (WS) to detect the risk areas for low and high daily volume (DV) of emergency calls. We use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 43 publications
0
24
1
2
Order By: Relevance
“…Contrary to the findings reported by other researchers [14][15][16][17][18][19][20][21][22][23], the current study did not confirm effects of environmental factors investigated, i.e., air temperature, atmospheric humidity, speed of wind, pressure and total daily precipitation in the incidence of cardiac events, either on halny days or on days preceding the onset of halny, as well as throughout the whole year in the consecutive months from January 2011 to December 2011. The findings showed no statistically significant correlations between the environmental variables and the number of cardiac events in any of the periods analysed (i.e., days with halny, days preceding halny onset, total days with and preceding halny, other days, all the days combined.)…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Contrary to the findings reported by other researchers [14][15][16][17][18][19][20][21][22][23], the current study did not confirm effects of environmental factors investigated, i.e., air temperature, atmospheric humidity, speed of wind, pressure and total daily precipitation in the incidence of cardiac events, either on halny days or on days preceding the onset of halny, as well as throughout the whole year in the consecutive months from January 2011 to December 2011. The findings showed no statistically significant correlations between the environmental variables and the number of cardiac events in any of the periods analysed (i.e., days with halny, days preceding halny onset, total days with and preceding halny, other days, all the days combined.)…”
Section: Discussioncontrasting
confidence: 99%
“…Based on a review of the literature it can be concluded that many researchers are investigating the association between wind-related environmental variables, and cardio-or cerebrovascular events, including the impact observed on days preceding onset of such weather conditions [14][15][16][17][18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the incidence of specific diagnoses has been correlated with meteorological data. One study has shown significant effects of cold and windy weather on the incidence of emergency calls regarding acute coronary syndrome or symptoms of elevated arterial blood pressure in an emergency medical service 2. Indeed, not only emergency medical service data but also emergency calling center data have shown that cold weather is often correlated with a higher incidence of hypertensive emergencies and acute coronary syndrome 1,2…”
Section: Introductionmentioning
confidence: 99%